Duration of asthma affects pulmonary function in asthmatic children - Gandaputra, Ellen P. (Universa Medicina, 2010)
Asthma is a common chronic disease and information on its management practices at the community level is helpful in identifying problems and improving asthma care. The prevalence of asthma in children below 18 years of age is around 9.3% and is on the increase. The aim of the present study was to determine the relationship between pulmonary function and duration of asthma in children. This was a cross-sectional study conducted at the outpatient clinic of RSUPN dr. Cipto Mangunkusumo in Central Jakarta. The study subjects were children aged 6-18 years with frequent episodic or persistent asthma. Among the 31 subjects there were 28 children with frequent episodic asthma and 3 children with persistent asthma. The duration of frequent episodic asthma ranged from 4 to 84 months, with a mean duration of 28 months. The FEV1 and V50 values decreased in proportion to the duration of asthma (p=0.003 and p=0.012, respectively). Mean FEV1 in persistent asthma was lower than that in frequent episodic asthma (82.7% vs. 61.2% at p=0.005). Similarly V50 and V25 were lower in persistent asthma, but the decrease was not statistically significant. The decrease in FEV1 and V50 values was proportional to the duration of asthma. The severity of asthma is indicative of inadequate asthma control, resulting in a proportional decrease in pulmonary function. Therefore prevention of asthmatic attacks is an essential feature of asthma management in children in order to enhance their quality of life.